Techno-economic analysis of a PV system with a battery energy storage system for small households: A case study in Rwanda - Nkuriyingoma, Obed; Özdemir, Engin; Sezen, Serkan (Frontiers in Energy Research, 2022)
Due to the inadequacy of distribution networks in developing countries, especially in small residential areas, there are frequent interruptions in the electrical energy provided by the grid. This problem negatively affects the life quality and productivity of the people living in these regions. This problem can be overcome by integrating a BESS-supported renewable energy source into the distribution system. This study presents a techno-economic analysis of a grid-connected solar PV system with BESS to supply a small community resident in Rwanda, Muhanga District, Shyogwe Sector using PV*SOL simulation software. The energy generated from the solar PV system is used to supply home appliances and water pumping system for agricultural activities. The simulation results show that the annual energy requirement is 82.34 MWh with a peak load of 30.4 kW. The simulation results reveal that a PV system, with an installed capacity of 57.33 kWp integrated with a BESS of 89.2 kWh storage capacity, can supply the load with own power consumption of 68.65%, a level of self-sufficiency of 64.38%, and a performance ratio of 86.05% when the desired ratio is set to 110% with the year as the reference period. The financial analysis a return on assets of 9.14% and an amortization period of 9.65 years. The results show that the proposed method is technically and economically feasible for solving the problem of electrical power outages in developing countries.